Development of an Interest- and Skill-Based Expert System for Student Career Decisions - Amin, Angger Nur; Riska, Suastika Yulia (LPPM STIKI Malang, 2024)
This study examines an expert system for assessing student career paths based on interests and competencies. This approach is intended to assist Informatics Engineering students in identifying a career trajectory that aligns with their profile. This system is anticipated to be an effective solution, given the growing demand for students to receive pertinent career guidance, as numerous students encounter difficulty in selecting a career path that aligns with their competencies. This expert system is developed by aggregating data concerning students' interests and skills, thereafter processed through the forward chaining approach to align facts and rules inside the knowledge base. Furthermore, the certainty factor approach is employed to assess the degree of certainty for each career recommendation provided. The algorithm can generate pertinent career recommendations depending on the student profile and the degree of certainty of the results. The system is evaluated against expert suggestions to verify the accuracy and relevance of the outcomes. The testing of several datasets indicates that the algorithm can deliver career suggestions aligned with expert outcomes. The findings indicate that 100% of the test outcomes align with the validation results provided by experts. So, this system can be a useful tool that helps students choose a job path and can also help with career counseling at schools.